Part I : Ranking of 2009 global livable cities index - Ang, Kenneth Fulian (2010)
In the past decade, technological advancements have accelerated globalization and increased the mobility of people, goods, capital and ideas across borders. This emphasizes the importance of the concept of livability and sustainability of global cities. The concept of quality of life and livability have received rising interests from academics and the public, however there is an absence of comprehensive studies involving ranking of livable cities.